Annual variation of insecticide properties of Peumus boldus on Sitophilus zeamais - Pérez, Felipe; Silva, Gonzalo; Tapia, Maritza; Hepp, Ruperto (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to determine the annual variation of Peumus boldus Molina insecticidal properties for the control of Sitophilus zeamais Motschulsky, under laboratory conditions. The powder of P. boldus leaves was evaluated, during 12 months, in 0.5, 1, and 2% (w/w) concentrations. Thirty-six treatments, with three replications, were evaluated in a completely randomized experimental design, with a factorial arrangement. Evaluations were made for adult and immature insect percentage mortality and emergence, grain weight loss and seed germination. The greatest mortality was obtained in August and September 2003, in the three concentrations with 100%, and the lowest mortality was registered in May 2003, when only 2% (w/w) reached almost 100% mortality. The lowest adult insect emergence and weight loss were obtained in the same treatments. The effect on immature stages was lower than on adults; and grain germination was affected by P. boldus powders. Insecticidal properties of P. boldus leaves powder are not stable during the year; May is the month with lesser insecticide efficacy; and the powder affects grain germination.
Keywords: maize weevil; stored grains; secondary metabolites